Assertiveness as a Critical Factor for Organisational Adaptability in Service SMEs - Sánchez-García, Jacqueline Y.; Núñez-Ríos, Juan E. (Emerald Publishing Limited, 2025)
Abstract To continue operating and seeking competitiveness in a complex and highly changing context, small- and medium-sized service companies (SMEs) depend heavily on their employees. Organisations must identify capabilities that allow them to respond quickly to environmental changes. This chapter empirically explores the impact of assertiveness on organisational adaptability (OA) and proposes a model with relationships oriented to foster adaptability, considering assertiveness as a relevant factor. Partial least squares structural equation modelling (PLS-SEM) was used to express and test the model hypotheses. Data were collected from 200 SMEs. The results show a strong and significant association between assertiveness, people development and organisational adaptation, suggesting that decision-makers can promote OA. This work may enable academics and managers to improve communication and inter-organisational relationships, allowing them to focus their strategies and resources to increase managerial and adaptive capacity and enhance performance and innovation.